A SYSTEM FOR THE UNIFORM DISTRIBUTION OF SYNTHETIC DOWN FILLER IN THE CHAMBER OF A TEXTILE PRODUCT USING MULTIDIRECTIONAL AIR JETS - LONSKYI, VITALII; KARMALITA, ANATOLII (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article investigates the problem of uneven distribution of synthetic down filler in the chamber of a garment part prior to the quilting operation. The filling process occurs using specialized equipment with compressed air. After passing through the nozzle, the microfibers of synthetic down clump together under the influence of compressed air within the chamber, significantly complicating further processing and necessitating additional manual preparation before quilting. An innovative solution is proposed in the form of a device to automate the distribution of the filler using multidirectional jets of compressed air with programmable pulses. Mounted on the nozzle of a down-filling machine, the device ensures uniform distribution of the filler by precisely adjusting the direction and pressure of the air based on the required particle displacement distance. The physical properties of synthetic down, such as its lightness, tendency to aggregate, and electrostatic effects, are analyzed, along with its aerodynamic characteristics: the mass-to-surface-area ratio, chaotic behavior in laminar flow, and the formation of vortex flows. Particular attention is given to the impact of turbulence, which aids in loosening the down but can lead to particle sedimentation if excessively intense. The process is modeled using principles of fluid and gas mechanics, specifically equations of aerodynamic drag and force equilibrium, taking into account air velocity and pressure, as well as the mass and density of the down. The device’s development aims to enhance production efficiency by reducing the time and costs associated with part preparation. Future research involves creating a prototype and conducting experimental validation to confirm theoretical calculations and assess the practical applicability of the development in real production conditions.
Keywords: synthetic down; compressed air; aerodynamic resistance; automation; turbulent flow; uniform distribution